The genus phillipsia from China and Thailand - Ekanayaka A. (2017)
© 2017 Magnolia Press. The genus Phillipsia (Sarcoscyphaceae) is characterized by large, bright-coloured, sub-stipitate apothecia, sub-operculate asci and asymmetrical ascospores with longitudinal striations. Morphological and phylogenetic studies were carried out on new collections of Phillipsia from China and Thailand. Phillipsia subpurpurea are recorded from China and Phillipsia gelatinosa from Thailand is introduced as a new species to science. Our new collections are confirmed to be divergent from other species of Phillipsia based on morphological examination and molecular phylogenetic analyses of ITS and LSU sequence data. Descriptions and figures are provided for the taxa which are also compared with allied taxa.